The efficacy of adalimumab in the treatment of hidradenitis suppurativa - Balevi, Ali; Üstüner, Pelin; Özdemir, Mustafa (My University, 2018)
Objectives: Hidradenitis suppurativa is seen as a result of the occlusion, constriction and bacterial infection of the apocrine glands in bilateral axillas, submammarian areas, neck, inguinal regions, flexural surfaces of the thighs and anogenital areas. Among the biological agents adalimumab is a recombinant human IgG1 monoclonal antibody; TNF-? antagonist approved to be used in the treatment of hidradenitissuppurativa. Methods: In this study, 12 patients resistant to conventional treatments with moderate severity, Hurley stage 2 or 3 were started subcutaneous adalimumab treatment. The disease activities upon the hidradenitis suppurativa, clinical severity index and life quality index of the patients were examined both before and 1 year after the treatment. Results: Twelve patients were recruited. In the examination of the hidradenitis suppurativa clinical severity scores, significant clinical responses were noted in 9 (75%) patients. While the mean value of the life quality index was 14.4±6.9 before the treatment, it was determined to be significantly decreased to 4.3±3.8 after the treatment. Conclusion: We concluded that adalimumab; the unique biological agent approved to be used in the treatment of treatment-resistant, moderate-severe hidradenitis suppurativa is efficient and safe in similar ratios with the previous clinical studies in the literature.

Amaç: Hidradenitis suppurativa; her iki koltuk altı, göğüs altları, boyun, kasıklar, bacakların birbirine sürten yüzünde ve anogenital bölgelerde apokrin bez kanalında tıkanma, daralma ve bakteriyel enfeksiyon sonucu görülmektedir. Biyolojik ajanlar arasında adalimumab; hidradenitis süpürativa tedavisinde kullanımı onaylanmış TNF-? antagonisti rekombinant insan IgG1 monoklonal antikorudur. Yöntemler: Bu çalışmada klasik tedavilere dirençli, orta-şiddetli tutulumlu, Hurley stage 2 veya 3, klasik tedavilere direnç/yetersizlik olan 12 hastaya adalimumab tedavisi uygulandı. Hastaların tedavi öncesi ve 1 yıllık tedavi sonrası hidradenitis süpürativa klinik şiddet indeksine göre hastalık aktiviteleri ve yaşam kalite indeksleri incelendi. Bulgular: Oniki hasta çalışmaya alındı. 7 hastada Hurley 3, geriye kalan 5 hastada Hurley 2 seviyesinde tutulum mevcuttu. Hidradenitis süpürativa klinik şiddet skorlaması incelendiğinde 9 hastada (%75) anlamlı klinik yanıt tespit edildi. Tedavi öncesi yaşam kalite indeksi ortalamasının 14.4±6.9 iken, tedavi sonrası anlamlı oranda gerileyerek 4.3±3.8'a düştüğü saptandı. Sonuç: Tedaviye dirençli orta-şiddetli hidradenitis süpürativa tedavisinde kullanımı onay almış tek biyolojik ajan olan adalimumabın literatürdeki önceki klinik çalışmalarla benzer oranda etkin ve güvenilir olduğu sonucuna vardık.
Hidradenitissüpürativa tedavisinde adalimumabın etkinliği
Keywords: Adalimumab; Eccrine Glands; Hidradenitis; Adalimumab; Ekrin Ter Bezleri; Hidradenit